Kontaminasi Residu Pestisida Organofosfat di Dalam Tanaman Holtikultura - Widia Purnamasari; Moch Irfan Hadi; Eva Agustina (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
Excessive use of organophosphate pesticides is becoming more common these days. This can affect the level of pesticide residues in farmers' crops. Excessive spraying of pesticides can result in environmental pollution both small and large scale. If excessive exposure to these pesticides can cause damage to the ecosystem. The purpose of this study was to determine the level of organophosphate pesticide residues found in horticulture plants. This research method is a systematic review, by analyzing various studies regarding the contamination of organophosphate pesticide residues in horticultural crops. There are 20 studies from within the country. The results obtained in the form of levels of pesticide residues that are still below the threshold of the BMR (Maximum Residue Limit) of pesticides determined by SNI. Two other studies show that no pesticide residue content was detected. Conclusion: This shows that the sample tested is still safe for consumption. Socialization and education about the doses of pesticide use and how to reduce levels of pesticides in horticultural crops are needed to reduce the risk of exposure to pesticides